Tips for pharmacology teaching - Ahmad Mohammadi-Farani (Tabriz University of Medical Sciences, 2020)
Pharmacology is a core and prerequisite course in major medical fields. In many academic centers, it is provided as a teacher-centered lecture course. In this article, I present twelve tips to help pharmacology teachers have more vital pharmacology classes. The tips are most useful for teachers who teach pharmacology as a traditional "preclinical" discipline and use lecturing as their main teaching method. Some of the tips presented can also be used for teaching in other lecture-based courses.